Механізм ціноутворення в системі оцінки інвестиційного потенціалу підприємств - Сіренко, І. М. (Ways to Improve Construction Efficiency, 2012)
The basic properties of investment potential. An principles according to which must be built assess investment potential. The general algorithm for evaluating the investment potential of the company ..